357. iQA: Quality assurance management software in hospital radiology. (December 2018) - Manco, L.; Fabbri, S.; Tonini, E.; De Metrio, D.; Gulinati, F.; Turra, A.
Abstract : Purpose: iQA takes its bases on the necessity to share QA (Quality Assurance) radiologic information among different professionals such as physician as responsible of technology, technicians and medical physicists. Our medical physics department is involved in the QA of radiologic equipment on several hospitals in the Ferrara district. Methods and materials: iQA is a web-based software with a client/server architecture achievable from different navigator browser. Each user has an account that allows to view and modify data according to his permission limited to his equipment. For each radiological center, the equipment (RX tube, workstation monitor, computed radiography (CR) and digital radiography (DR) detectors, magnetic resonance) are listed with their location and technical information. Details on QA protocols and reports, status of maintenance, final evaluation to clinical use are always available. In case of some parameters are out of tolerance an alert is provided to the user by e-mail. Results: The use of iQA started from December 2017, after a training of each professional involved. From the beginning it results so useful to a real time monitoring of the equipment status. Conclusion: The future developments see the implementation in iQA of the nuclear medicine, radiotherapy equipment and also a radioprotection module. It could be develop iQA mobile application to enhance the users feedback.